Comparison of Endoscopic Ultrasound-Guided Fine-Needle Aspiration and Biopsy Device for Lymphadenopathy - Yuki Tanisaka; Masafumi Mizuide; Akashi Fujita; Tomoya Ogawa; Ryuichiro Araki; Masahiro Suzuki; Hiromune Katsuda; Youichi Saito; Kazuya Miyaguchi; Tomoaki Tashima; Yumi Mashimo; Masami Yasuda; et al. (Gastroenterology Research and Practice)
Background. Accurate diagnosis of benign and malignant lymphadenopathy is important for determining the appropriate treatment and prognosis. This study evaluated the diagnostic accuracy and usefulness of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) with a conventional needle compared to endoscopic ultrasound-guided fine-needle biopsy (EUS-FNB) with a Franseen needle for diagnosing lymphadenopathy. Methods. Patients who underwent EUS-FNA or EUS-FNB for mediastinal or abdominal lymphadenopathy between July 2013 and August 2020 were enrolled in the study. The outcomes between EUS-FNA patients (July 2013 to January 2017; 22-gauge conventional needle; Group A) and EUS-FNB patients (February 2017 to August 2020; 22-gauge Franseen needle; Group B) were compared. Results. A total of 154 patients (Group A: 83; Group B: 71) were analyzed. The diagnostic accuracy (differentiating between malignant and benign lesions) was 88.0% (95% confidence interval [CI], 79.2–93.3%) in Group A and 95.8% (95% CI, 88.3–98.8%) in Group B. Group B had high diagnostic accuracy, but there was no difference between the groups (p=0.14). Group B had significantly fewer passes (median 2, interquartile range (IQR): 2-4) than Group A (median 3, IQR: 3-4) (p<0.001). No procedural adverse events occurred in either group. Conclusions. Although the diagnostic accuracy between the groups was not statistically significant, EUS-FNB with a Franseen needle provided high diagnostic accuracy and required fewer passes to establish a diagnosis. Thus, EUS-FNB is useful for diagnosing lymphadenopathy.